Effects of Extraction Temperature on Polyphenol Compounds and Antioxidant Activity of Golden Bladderwort (Utricularia aurea) - Sabri Sudirman; Ace Baehaki; Fajar Fathullah; Miftahul Janna (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2023)
The excess of free radicals is known to induce dysfunction in tissues and cells within the human body. This phenomenon is caused by the imbalance between antioxidants and free radical production necessitating the need for exogenous antioxidants. Golden bladderwort (Utricularia aurea) plant may have the potential as a source of antioxidant. Therefore, this study aimed to investigate the effect of extraction temperature on the polyphenol compounds and the antioxidant activity of the golden bladderwort plant. The dried powder from the plant was extracted using 70% ethanol at 30, 45 and 60 ºC, with each treatment repeated three times. The antioxidant activity was analyzed by using the 2,2-diphenyl-1-picrylhydrazyl method. The results showed that the yield of extraction was 1.34% (30 ºC), 4.00% (45 ºC) and 12.48% (60 ºC). The total polyphenol and flavonoid contents found at 60ºC were 50.80 mg QE/g dried sample and 60.01 mg QE/g dried sample, respectively. Furthermore, the antioxidant activity was calculated in half-maximum inhibitory concentration (IC50 ), and the values obtained were 0,38 mg/mL (45 ºC), 0,35 mg/mL (30 ºC) and 0,11 mg/mL (60 ºC). These results indicated that temperature of extraction affected the level of polyphenol contents and the antioxidant activity of the golden bladderwort extract. The high extraction temperature (60 ºC) emerged as the most optimal condition for extraction with effective antioxidant activity. Therefore, the results can be used as a reference for future investigations involving the extraction of polyphenol compounds from golden bladderwort as a source of natural antioxidants.